PENGARUH REPUTASI AUDITOR DAN DEWAN DIREKSI TERHADAP PENGUNGKAPAN RESIKO PERUSAHAAN (Studi Empiris pada Perusahaan Industri yang Terdaftar pada Bursa Efek Indonesia Tahun 2016 - 2021) - Ernia Wati; Debby Katleya Zahra Salsabilla; Ardita Nafia Nur Apriliyanti; Cici Wardiati; Bima Cinintya Pratama (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
Abstract This study aims to determine the effect of the reputation of the Auditor and the Board of Directors on the Company's Risk Disclosure. The annual report data of industrial sector companies listed on the Indonesia Stock Exchange for the 2016-2021 period is used as a sample in this study. In this study, purposive sampling technique was used in sampling so that a sample of 18 companies was obtained with a total of 90 data that met the criteria. In this study also used multiple regression assisted using SPSS in performing data analysis techniques. The results of this study indicate that the reputation of the Auditor and the Board of Directors has a positive effect on the Company's Risk Disclosure. Keywords : Auditor Reputation, Board of Directors, Corporate Risk Disclosure